Education, Attitudes, and Language of Higher Education: Francophone Students in Northern Ontario - Wilkinson, Derek (Canadian Journal of Higher Education, 1994)
Data from 1586 Francophone students in Northeastern Ontario concerning their attitudes towards French and English show seven independent factors affect linguistic beliefs. Three factors -believing French unimportant, believing English practically dominant, and believing their French inadequate - lead students to continue their post-secondary education solely in English. Believing French more pleasurable is positively, and believing English superior is negatively, related to continuing post-secondary education solely in French. Educational level is negatively related to believing English superior and to believing French unimportant but positively related to believing English dominant, French pleasurable, and their French inadequate. Policy should therefore focus on countering the belief in English dominance and the belief in the inadequacy of their ability in French.